Mullite–Silicate Proppants Based on High-Iron Bauxite and Waste from Metallurgical Industry in Kazakhstan - Tolebi Dzhienalyev; Alla Biryukova; Bagdaulet Kenzhaliyev; Alma Uskenbaeva; Galiya Ruzakhunova (Ceramics)
The suitability of microsilica as a raw material for the production of ceramic mullite–silicate proppants was assessed. The chemical and mineralogical compositions of the initial materials were studied. The mineral composition of bauxite is mainly represented by gibbsite Al(OH)3 and, to a lesser extent, kaolinite Al4[Si4O10](OH)8, with impurities of hematite and quartz. It is established that, in order to obtain mullite–silicate proppants, compositions containing 10–20% microsilica are optimal. The sintering of these compositions occurs at 1350–1380 °C. A lightweight ceramic proppant was obtained with a bulk density of 1.21–1.41 g/cm3, breaking ratio at 51.7 MPa of 19.1–20.3%, and sphericity and roundness of 0.7–0.9, and the optimal roasting temperature was determined as 1370–1380 °C.